Preparing Teacher Candidates for the Instruction of English Language Learners - Monica Marie Gonzalez (Networks: An Online Journal for Teacher Research, 2016)
This inquiry utilizes a sheltered instruction approach to lesson planning with the intention of improving teacher candidates’ instruction to English Language Learners (ELLs). In this study a web-based questionnaire and a sheltered instruction lesson plan template were used to facilitate opportunities for teacher candidates to reflect on and practice planning English for Speakers of Other Languages (ESOL) instruction. Data collections used were nine web-based questionnaire responses and thirty sheltered instruction lesson plans. Findings suggest teacher candidates need more experiences with using ELLs’ language proficiency data for instruction and need to learn how to use rubrics when giving ELLs feedback on their assignments.
Keywords: sheltered instruction; preservive; English Language Learners; inquiry